A disturbance suppression micro-Newton force sensor based on shadow method. (March 2023) - Yang, Yong; Zhao, Meirong; Li, Dantong; Tao, Moran; Zhu, Chunyuan; Zheng, Yelong; Tian, Yu
Abstract: The precision of micro-force measurement depends on the force sensor sensitivity and the environmental disturbance magnitude. However, micro-force sensors generally have the poor anti-disturbance ability. Inspired by the shadow formed by water striders walking on water surface under sunlight, a viscoelastic-polymer micro-force (VPMF) sensor based on the shadow method was proposed, which could suppress disturbances effectively due to the high damping ratio of 0.22. The shadow diameter change and the applied force were proportional. The experimental results indicated that the sensitivity could reach 2.15 μ N/pixel with a good linear performance. Furthermore, compared with the cantilever, it was capable of the reduction of the disturbance influence by approximately 96.35%. Therefore, the VPMF sensor can be applied to reliable micro-force measurement in complex environments such as industrial sites. Graphical abstract: Highlights: The overall design of a viscoelastic-polymer micro-force sensor is presented. The shadow method for micro force and displacement measurement is derived. The viscoelastic polymer is introduced to improve the anti-disturbance ability. The force sensitivity of the sensor was 2.15 μ N/pixel with a range of 0.981 mN. The displacement sensitivity was 13.5 nm/pixel with a range of 7 μ m .